2022
DOI: 10.3389/fgene.2022.934196
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Ferroptosis-Related lncRNA Model Associated With Immune Infiltration in Colon Cancer

Abstract: Colon cancer (CC) is a common malignant tumor worldwide, and ferroptosis plays a vital role in the pathology and progression of CC. Effective prognostic tools are required to guide clinical decision-making in CC. In our study, gene expression and clinical data of CC were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. We identified the differentially expressed ferroptosis-related lncRNAs using the differential expression and gene co-expression analysis. Then, univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Ferroptosis-related genes are closely related to the treatment and prognosis of CRC. By analyzing the expression and clinical characteristics of lncRNA in TCGA-COAD and GEO databases, three differentially expressed ferroptosis-related lncRNAs (XXbac-B476C20.9, TP73-AS1 and SNHG15) were identified as biomarkers to establish a prognostic model of CC patients [33] and complete the treatment system. Han et al [34] explored the transcriptome profile of lncRNA in primary CRC tissues and corresponding paired adjacent non-tumor tissues by RNA-seq, and found that LINC00239 was significantly overexpressed in colorectal cancer tissues.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Ferroptosis-related genes are closely related to the treatment and prognosis of CRC. By analyzing the expression and clinical characteristics of lncRNA in TCGA-COAD and GEO databases, three differentially expressed ferroptosis-related lncRNAs (XXbac-B476C20.9, TP73-AS1 and SNHG15) were identified as biomarkers to establish a prognostic model of CC patients [33] and complete the treatment system. Han et al [34] explored the transcriptome profile of lncRNA in primary CRC tissues and corresponding paired adjacent non-tumor tissues by RNA-seq, and found that LINC00239 was significantly overexpressed in colorectal cancer tissues.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Ferroptosis, identified as a unique form of non-apoptotic and non-necrotic cell death, is considered a potential therapeutic target in several malignancies (13). The aberrant expression and dysfunction of iron death-related lncRNAs have been associated with prognosis, tumor progression and metastasis in colorectal cancer, suggesting their potential as novel biomarkers and therapeutic targets (14)(15)(16). Evidence has shown that iron death-related lncRNAs have specific expression patterns in colorectal cancer tissue and are closely associated with disease progression and prognosis (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that iron death-related lncRNAs have specific expression patterns in colorectal cancer tissue and are closely associated with disease progression and prognosis (11,12). However, despite the increasing volume of research, the exact molecular mechanisms, biological functions and associations with clinical features of iron death-related lncRNAs in colorectal cancer are still controversial (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%